Vertical controlled landing on 67P / Churyumov-Gerasimenko. (1st November 2020) - Probst, A.; San Martín, A.; Zimmer, A.; Broschart, S.; Förstner, R.
Abstract: With the increasing interest of small body science due to its important role in the puzzle of the solar system formation, missions to small bodies are studied and developed in preparation for future exploration. Together with the operational experience gained and the general rapid technology development, landers and surface mobility elements enable more and more an enhancement of the scientific mission return by collecting in-situ measurements or samples of the surface. Hence, the descent and landing operations become a vital part in a successful execution of the mission. In this paper, a descent strategy for a vertical landing on small bodies is presented. A controlled descent and landing sequence is proposed as opposed to ballistic descents used in previous small body landers (Ulamec and Biele, 2009). The analysis aims for a generic investigation of the surface accessibility of a small body on the example of the comet 67P/Churyumov-Gerasimenko . A vertical controlled descent trajectory concept is proposed and applied to all surface facets of the downscaled ESA polyhedron shape model (released in 2015 (ESA, 2015)). The trajectories are assessed by their duration of descent, Δ v need and their surface accessibility with respect to safety distances to the surface and the canyon walls. The analysis results in Δ v need ranges between Δ v m i n = 0.7 m s −1 and Δ v m a x = 3.1 m s −1, the duration of descent between t m i n = 65 min and t m a x = 275 min. If a minimum distance of 175 ​m to the canyon surface or walls is considered as safe, 90% of the comet's surface is accessible with the described implemented strategy. Highlights: The paper presents an approach for successful vertical controlled landing on small gravitational bodies. It highlights the feasibility of this concept by taking into account security aspects during descent and landing. It gives estimates the surface accessibility that can be achieved even for complex regions such as canyons and valleys. The results are important for future mission concepts 0.